NIKE, FUTEBOL E PROPAGANDA: A produção publicitária no Brasil em tempo de Copa do Mundo - OLIVEIRA, FABIO ELOI DE (2020)
The central theme of the research is the advertising communication study of Nike during the World Cup period in Brazil, and specially the commercials produced for the world championships between 2006 and 2018, period that Nike's communication, based on specific objectives, is characterized by elements of what the brand itself and the Brazilians imagine as national culture. The purpose of this analysis is to understand how these cultural elements work to develope the idea of belonging and the spectator identification with the Brazilian National Team, and consequently with the sponsor. In methodological perspective the research is guided by Depth Hermeneutics (John B. Thompson) to incorporate the study of the content advertising produced by Nike during that period. The thesis is also part of the theoretical and epistemological concerns studied by the discussion group Understanding as a Method, linked with the Postgraduate Program in Social Communication of Methodist University of São Paulo (Umesp). The study has theoretical references supported by documentary research and the descriptive narrative method, essentially applied to the advertising pieces presentation that compose the corpus research. The purpose of the thesis is to support to understand how global companies breed cultural identifications in different parts of the Planet from a process of glocalization based on communication.